Associations between medication use and functional gastrointestinal disorders: a population‐based study. Issue 5 (29th January 2013) - Choung, R. S.; Locke, G. R.; Schleck, C. D.; Zinsmeister, A. R.; Talley, N. J.
Abstract Background Functional GI syndromes are known to be very prevalent, but this may be linked to unrecognized medications use. We aimed to estimate the prevalence of PPI, antidepressant, and narcotic use in the general population, and to evaluate the association between each medication and functional GI syndromes adjusting for potential confounders. Methods In 2008 and 2009, newly revised versions of a validated bowel disease questionnaire were mailed to a community‐based cohort (total mailed = 8006) of Olmsted County, MN residents; 3831 returned the questionnaire (response rate = 48.0%). Medication usage, specifically PPIs, narcotics, and antidepressants in the last year, was elicited via three separate questions on the questionnaire. The association between each medication and GI symptom complexes was assessed using multiple variable logistic regression models. Key Results A total of 3515 of the respondents (92%) had complete data (mean age: 61 ± 15; 54% female). The overall proportion reporting PPI use was 20% (95% CI: 19, 22), narcotic use 12% (95% CI: 11, 13), and antidepressant use 15% (95% CI: 14, 16). PPI use was significantly associated with IBS status (OR = 1.4, 95% CI 1.1, 1.7) as well as with GERD (OR = 3.5, 95% CI 2.7, 4.4) and dyspepsia (OR = 2.0, 95% CI 1.5, 2.7). The association of PPI use with IBS was not explained by coexistent GERD or dyspepsia. Antidepressant use was significantly associated only with bloating (OR = 1.6, 1.1, 2.2). Conclusions & Inferences Some medications that may alter intestinal transit or bowel flora are commonly utilized by the general population, and PPI use appears to be linked to IBS.